Melancholy in Lachrimae Coactae by John Dowland (Per Musi, 2017)
The melancholic mood was widespread in England since the 16th Century. Thus, the majority of English musical pieces contained melancholic figures. John Dowland is one of the main leaders on the Elizabethan melancholy and he used several rhetoric artifices to represent it in his works. One of his most representative melancholic works in this respect is Seven Tears or Lachrimae. This article approaches the fifth pavane, Lachrimae Coactae, through rhetoric analysis from the perspective of the Elizabethan melancholy in music. Coactae is the apex point of soul’s suffering, that is, apostasy. For this representation, we found some exorbitance, like the massive use of chromaticism and fictae. Additionally, it synthesized each one of the affections proposed by the previous pavanes.